Про хінтінг шрифтів - Сальнікова, Т. С. (ХНУРЕ, 2021)
For fonts to look good on screen at all sizes, they need to be optimized - a process called hinting. You can correct the position of the contour on the pixel grid using special algorithms and manually. Hints are pairs of guides that additionally define the position and thickness of the main strokes (elements) of a symbol. They are implemented as a set of pairs of vertical and horizontal lines that capture all strokes (and similar elements) of the characters. Hinting is an essential part of the production of a quality font. It is indispensable in every font intended to be legible at small sizes on low resolution output devices. A well -hinted font offers the quality only provided in the past by hand-tuned bitmaps –but with all the speed and reduced memory requirements which characterize outline font formats. Moreover, because the bitmaps are still produced by an outline font, text can be rotated, scaled and viewed at different sizes, and even printed out while maintaining high image quality.
Keywords: шрифт; друк